2014
DOI: 10.1126/science.1254738
|View full text |Cite
|
Sign up to set email alerts
|

Early 56 Ni decay gamma rays from SN2014J suggest an unusual explosion

Abstract: Type-Ia supernovae result from binary systems that include a carbon-oxygen white dwarf, and these thermonuclear explosions typically produce 0.5 M ! of radioactive 56 Ni. The 56 Ni is commonly believed to be buried deeply in the expanding supernova cloud. Surprisingly, in SN2014J we detected the lines at 158 and 812 keV from 56 Ni decay (τ~8.8 days) earlier than the expected several-week time scale, only ~20 days after the explosion, and with flux levels corresponding to roughly 10% of the total expected amou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
184
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 137 publications
(194 citation statements)
references
References 54 publications
(50 reference statements)
8
184
2
Order By: Relevance
“…INTEGRAL could detect the long awaited gamma-ray signatures of the thermonuclear runaway, through the early emission from the decay of 56 Ni (mean lifetime τ 8.8 days) about 20 days after the explosion, and the main gamma-ray lines at 847, 1238, and 511 keV from the decay of 56 Co (τ 111 days). These data suggested either a surface explosion or some unusual morphology of the runaway [44,45,53,54,76], either case in stark contrast to the conventional Chandrasekhar model. Clearly, the glimpse offered by SN2014J observations underlines the importance of gamma-ray line diagnostics in these systems and emphasize that more and better observations hold the key to a deeper understanding of how the thermonuclear explosion of a white dwarf star unfolds.…”
Section: Antimatter and Wimp Dark Mattermentioning
confidence: 46%
“…INTEGRAL could detect the long awaited gamma-ray signatures of the thermonuclear runaway, through the early emission from the decay of 56 Ni (mean lifetime τ 8.8 days) about 20 days after the explosion, and the main gamma-ray lines at 847, 1238, and 511 keV from the decay of 56 Co (τ 111 days). These data suggested either a surface explosion or some unusual morphology of the runaway [44,45,53,54,76], either case in stark contrast to the conventional Chandrasekhar model. Clearly, the glimpse offered by SN2014J observations underlines the importance of gamma-ray line diagnostics in these systems and emphasize that more and better observations hold the key to a deeper understanding of how the thermonuclear explosion of a white dwarf star unfolds.…”
Section: Antimatter and Wimp Dark Mattermentioning
confidence: 46%
“…We then fix the shapes of the spectral templates during one orbit of the selected data set and scale the amplitude of each component for the entire Ge camera by pointing to properly trace intensity variations of each background component. Long-term investigations showed that the relative intensities of a particular spectral background feature present in one detector with respect to the mean intensity of the same feature in all detectors (detector ratios) are constant in time and thus are maximally independent of possible celestial signals (Diehl et al 2014(Diehl et al , 2015 1 . Therefore, the spectral shape and detector ratio constancy that is expected for each individual background component is imprinted onto the shortterm (pointing-to-pointing) variations, while the mean amplitude (over all detectors) of a particular spectral feature is still allowed to vary to normalize the predicted background count rate.…”
Section: Background Modelingmentioning
confidence: 99%
“…The general results from INTEGRAL, which detected the 847 and 1238 keV γ -ray lines of radioactive 56 Co (Churazov et al 2014(Churazov et al , 2015Diehl et al 2014Diehl et al , 2015, showed that the general nickel distribution was stratified with a total 56 Ni mass of ∼0.5 M . Due to the low signal to noise, there is some ambiguity about just how to interpret the results, that is, whether the γ -rays favour symmetric nickel distributions (Churazov et al 2014(Churazov et al , 2015 or whether the lines are significantly Doppler-broadened asymmetric ones (Diehl et al 2014(Diehl et al , 2015. We are not terribly sensitive to small asymmetries, and therefore we cannot distinguish between these different interpretations.…”
Section: O M Pa R I S O N W I T H Smentioning
confidence: 99%
“…modern SN Ia, SN 2014J has been extremely well observed: in γ -rays (Churazov et al 2014;Diehl et al 2014), X-rays (Margutti et al 2014), by Hubble Space Telescope Kelly et al 2014), optical (Amanullah et al 2014;Ashall et al 2014;Goobar et al 2014;Nielsen et al 2014) at high resolution (Welty et al 2014;Graham et al 2015;Jack, Baron & Hauschildt 2015;Ritchey et al 2015), near-infrared (near-IR; Friesen et al 2014;Marion et al 2015), mid-IR (Johansson et al 2014;Telesco et al 2015), polarimetry (Kawabata et al 2014), with rapid photometry (Siverd et al 2015), and in radio (Pérez-Torres et al 2014).…”
mentioning
confidence: 99%